A Model of Vaccine Coverage Promotion in Children Aged 0-5 Years in Yala - หะยีอีแต, อีระฟาน; หลังปูเต๊ะ, ประภาภรณ์ (Al-HIKMAH Journal, 2020)
In 2018, the morbidity and mortality from measles among children aged 0-5 years in Yala Province was ranked at the highest number of the country. It was due to a lower rate of measles vaccine coverage in the area. This mixed method study was aimed at 1) investigating health belief pattern of the parents, who their children did not meet the fully vaccine coverage, on vaccine preventable diseases and 2) developing a model of vaccine coverage promotion for children aged 0-5 years. A Total of 75 parents were included in a survey research. The health belief pattern questionnaire was validated by 3 experts and the Item Objective Congruence Index was 1 and the Cronbach’s alpha reliability was 0.81. In addition, a total of 87 people including community and religious leaders, pre-school teachers, village health volunteers, and public health staff involved in a participatory action research. The data were analyzed by using descriptive statistics for survey part and thematic analytics method for qualitative part. The results shown that the health belief pattern of the parents was ranked at fair level which was not enough to lead them in bringing their children for vaccination. The model of vaccine coverage promotion consisted of 1) Quality service improvement, 2) Communication with community, and 3) Participation of community. After the implementation of the model, the public health staff had gained knowledge and skills on immunization service, the community leaders also acknowledged the problems and participated in vaccine coverage promotion activities and the children were increasingly brought for vaccination.